The relationship between job satisfaction, individual moral reasoning and organizational factors with whistleblowing practice in public sector / Nur Farah Fareena Roslan - Roslan, Nur Farah Fareena (2019)
Whistleblowing is a report on any corporate wrongdoing that occurs in organisations. There are many companies that bankrupt or suffer loss due to unethical behaviour such as mismanagement, misuse of company funds, money laundering, and manipulation of income statement for private advantage without considering the employees’ or shareholders interest. This study is conducted to examine the factors that could motivate whistleblowing practices in public sector. Several predictive variables have been considered, such as individual and organizational factors. This research aimed to discuss the influence of job satisfaction, individual moral reasoning and organizational factors with whistleblowing practice in public sector. The survey data were taken from 152 employees in Majlis Daerah Kampar, Perak. The results showed that job satisfaction has a significant negative effect on whistleblowing practice. Moreover, individual moral reasoning and organizational factors has significant positive effects that can help to strengthen the relationship on whistleblowing practice. The implications and suggestions are discussed.